2021
DOI: 10.1007/s43630-021-00024-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the vibrational marker of tyrosine cation radical using ultrafast transient infrared spectroscopy of flavoprotein systems

Abstract: Tryptophan and tyrosine radical intermediates play crucial roles in many biological charge transfer processes. Particularly in flavoprotein photochemistry, short-lived reaction intermediates can be studied by the complementary techniques of ultrafast visible and infrared spectroscopy. The spectral properties of tryptophan radical are well established, and the formation of neutral tyrosine radicals has been observed in many biological processes. However, only recently, the formation of a cation tyrosine radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…Significantly, this spectrum is characterized by the appearance of a new transient at ∼1528 cm –1 which is a vibrational marker for the neutral semiquinone FADH • species (NSQ) that is also observed in flavodoxin and glucose oxidase. 32 , 33 In EADS3, the FADH • transient at 1528 cm –1 increases in amplitude with a time constant of 24 ps and relaxes in 184 ps. On this timescale the FAD* continues to decay, consistent with the complex multiexponential kinetics observed in other BLUF domains, 29 and there is a similarly complex evolution in the region of the FAD C=O bleach modes, suggesting underlying dynamics in protein modes.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, this spectrum is characterized by the appearance of a new transient at ∼1528 cm –1 which is a vibrational marker for the neutral semiquinone FADH • species (NSQ) that is also observed in flavodoxin and glucose oxidase. 32 , 33 In EADS3, the FADH • transient at 1528 cm –1 increases in amplitude with a time constant of 24 ps and relaxes in 184 ps. On this timescale the FAD* continues to decay, consistent with the complex multiexponential kinetics observed in other BLUF domains, 29 and there is a similarly complex evolution in the region of the FAD C=O bleach modes, suggesting underlying dynamics in protein modes.…”
Section: Resultsmentioning
confidence: 99%
“…We are happy to announce that today, this virtual volume unites 18 contributions by scientists from 17 countries (Canada, Czech republic, Finland, France, Germany, Hungary, India, Italy, Japan, Lebanon, Poland, Russia, Spain, Switzerland, Taiwan, UK, US) touching upon the wide variety of the subjects dealt with by Klaus at various times [25,[127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143].…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
“…In a mutated variant, they observed that no exchange occurs between different configurations on the timescale up to at least 2 ns, despite the presumed flexibility of the quenching residue Trp214. In a related study, a Hungarian-French-British collaboration used the same protein (along with some other flavoproteins) to establish the vibrational marker of the recently discovered tyrosine cation radical by ultrafast transient infrared spectroscopy [132].…”
Section: Legacy Tribute Continuation…mentioning
confidence: 99%
“…TrmFO is a bacterial flavoenzyme that is not photocatalytic, but has recently become a model system for flavin photoreduction [14,15,22]. It is involved in post-transcriptional site-specific methylation of tRNA, further using C 2 H 4 folate as a carbon donor substrate and NADPH as a flavin-reducing substrate [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of the cysteine, the flavin fluorescence is strongly quenched by ET from the close-by (3.3 Å ring-to-ring) tyrosine residue. This feature has allowed to show that tyrosine radicals can be formed and spectroscopically characterized in the visible [15] and infrared [22], in the elusive TyrOH •+ state, which has been invoked as a potential functional intermediate in biochemical reactions [28,29].…”
Section: Introductionmentioning
confidence: 99%